PEMBERDAYAAN EKONOMI PEREMPUAN BERBASIS MAJLIS TA’LIM MELALUI STRATEGI PEMASARAN HOME INDUSTRY KERUPUK - Siti Rumilah; Ummiy Fauziyah Laili (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
This community service program is a form of campus academic activities to help overcome the economic problems of rural communities, especially village women who in fact in terms of the economy are less productive. The main aim of this program is to increase the economic potential of village women based on Majlis Ta'lim. This is done to face the challenges for Small and Medium Enterprises (UKM) to increase competitiveness through increasing productivity and quality of products according to the Indonesian National Standard (SNI), especially for rural home industries, especially women farm laborers to use their time optimally to improve family welfare. They not only rely on rice fields (tandur) and the harvest period, which is approximately three months' waiting period. They not only depend on the natural and environmental conditions that exist, but also are able to take advantage of the existing potential to make a more economic contribution to the household. With the ABCD method, the companion made a change of mindset while conducting marketing strategy training on the production of crackers which had been carried out by several members of the Ta'lim Assembly, by providing training in marketing strategies with product targets, distribution, pricing, and promotion strategies that had followed developments ( on line marketing), so that the selling power increases. Paying attention to the SWOT analysis, namely strengths, weaknesses, opportunities, and threats can generally be overcome because the people in Bakalan Village, Grogol Subdistrict, Kediri Regency, especially Majlis Ta'lim Muslimah have a strong and maintained network of friendship through routine recitation, so that this economic activity remains can be done.